Business Development Strategy in the Jiwel Asli Mirasa Traditional Food Business Field Using SWOT Analysis and Business Model Canvas - Darmawan, Gugun; Herlinawati, Erna; Muttaqin, Ridlwan (Dinasti International Journal of Digital Business Management, 2024)
This research aims to identify and analyze business development strategies that can be applied to the culinary food business “Jiwel Asli Mirasa”. The analysis method used in this research is SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and Business Model Canvas. Data were collected through interviews with business owners, direct observation, and case studies related to the culinary food industry. The results of the SWOT analysis identified internal strengths, such as the authenticity of product flavors and strategic location, as well as weaknesses, such as limitations in marketing and business development. On the other hand, external opportunities such as growing market demand for local culinary food and threats such as competition from established competitors were identified. Next, the Business Model Canvas was used to describe the current business model of “Jiwel Asli Mirasa” and evaluate key elements such as customer segments, value proposition, distribution channels, and key resources. Based on the results of the SWOT analysis and Business Model Canvas, several business development strategies are recommended, including product diversification, increasing marketing efforts through social media and cooperation with partners, and increasing product innovation. The implementation of these strategies is expected to help “Jiwel Asli Mirasa” to strengthen its market position and achieve sustainable growth in the culinary food industry.